МЕТОД РОЗПОДІЛЕННЯ ІЄРАРХІЧНОГО МЕТАГРАФА НА РІВНІ - Кривенко, Александра Сергеевна; Штогрина, Елена Сергеевна; Терновой, Максим Юрьевич (Збірник матеріалів Міжнародної науково-технічної конференції «ПЕРСПЕКТИВИ ТЕЛЕКОМУНІКАЦІЙ», 2016)
Layer assignment method for hierarchical metagraph This paper describes the method of automatic layer assignment for hierarhical metagraphs. The method walks through paths in metagraph and numerates nodes layers. Metavertices and inner vertices are always assigns to the same layer. Layer assignment method can be used as first step for metagraph visualization method.